PATHOPHYSIOLOGY OF THE LUNGS AND RELATED DISEASES - Temirova Dilnoza Valiyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:The lungs are essential for gas exchange and play a crucial role in maintaining  oxygenation  and  acid-base  balance  in  the  body.  Pathophysiological changes  in  lung  tissue,  airways,  and  pulmonary  circulation  can  lead  to  various respiratory  diseases,  including  chronic  obstructive  pulmonary  disease  (COPD), asthma, pulmonary fibrosis, and lung infections. This article explores the mechanisms underlying  lung  pathophysiology  and  the  impact  of  these  diseases  on  respiratory function.